A case of pustular psoriasis in a young boy / Meera Kuppusamy and Tarita Taib. - Kuppusamy, Meera; Taib, Tarita (Universiti Teknologi MARA Cawangan Selangor, 2017)
We report a case of a 13-year-old boy who presented with acute onset of generalised erythematous skin and patchy areas of pustules for one week duration. He was well until one month ago when he started having small scaly plaques on his scalp and extensors of his legs. During the acute episode, he also had joint pain and bilateral conjunctivitis. Skin biopsy confirmed pustular psoriasis. He developed leucocytosis and transaminitis during the acute phase of the pustular eruption while on acitretin, which was then withheld. Subsequently, treatment with oral cyclosporine induced remission of his skin and joint disease. The case is hereby reported because of rarity of presentation and clinical features. Oral cyclosporine should be considered in patients with generalised pustular psoriasis complicated with transaminitis.